Bilateral diffuse temporal bone osteoradionecrosis: a diagnostic and therapeutic challenge - Orfao, Joao; Carvalho, Liliana; Pedrosa, Gustavo; Durão, Carolina; Boavida, Margarida; Barbosa, Leonel; Freire, Filipe (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Temporal bone osteoradionecrosis (TBORN) is a rare complication of head and neck radiotherapy. It usually presents as a unilateral disorder with a long latency between the exposition to radiation and the symptoms onset, which might overlap with other clinical entities, making it difficult to establish the diagnosis. It can be classified as localized, when confined to the tympanic bone; or diffuse, when extended to other portions of the temporal bone, with the inherent implication in treatment selection and prognosis. The authors present a case of a 53 years old patient with multiple comorbidities, including an immunosuppressive state, who presented an infected massive diffuse TBORN bilaterally. The diagnosis was challenging and the patient was initially treated for a malignant otitis externa, but after established diagnosis of TBORN, the patient was treated resorting to surgery, topical treatment and hyperbaric oxygenotherapy, with consequent symptoms resolution. This case illustrates the difficulty in establishing the diagnosing and treatment of TBORN and highlights the importance of a low suspicion threshold for this rare complication of radiotherapy, for which there is still no consensus regarding the best treatment.